2004
DOI: 10.1159/000077992
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 Is Increased in the Breath Condensate of Patients with Non-Small-Cell Lung Cancer

Abstract: One recent line of cancer research is currently directed to the study of growth factors. Of increasing interest is endothelin-1 (ET-1), a mitogenic factor already investigated in several human cancer cell lines, which has been found to participate in the development and progression of tumours. This peptide has an important role also in non-small-cell lung cancer (NSCLC) where ET-1 expression has been found in 100% of cell lines. Objectives: The aim of this study was to measure ET-1 concentrations in the airway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 14 publications
3
32
0
Order By: Relevance
“…The level of ET-1 increased as the disease progresses; this finding is consistent with that of Carpagnano et al (24) and Boldrini et al (25). This tendency indicated that ET-1 induces the growth and metastasis of lung cancer.…”
Section: Discussionsupporting
confidence: 91%
“…The level of ET-1 increased as the disease progresses; this finding is consistent with that of Carpagnano et al (24) and Boldrini et al (25). This tendency indicated that ET-1 induces the growth and metastasis of lung cancer.…”
Section: Discussionsupporting
confidence: 91%
“…As a completely non-invasive procedure, exhaled breath condensate (EBC) has been extensively studied in order to explore respiratory pathophysiology and its clinical relevance in the diagnosis and treatment of a variety of respiratory diseases, including asthma, chronic obstructive pulmonary disease, allergic rhinitis, pneumonia, adult respiratory distress syndrome, lung sarcoidosis, malignant lung tumours, cystic fi brosis, idiopathic lung fi brosis, and tuberculosis (1)(2)(3).…”
mentioning
confidence: 99%
“…Other studies have demonstrated that interleukin2, TNF alpha, leptin, and endothelin-1 are present in higher levels in the EBC from LC patient compared to normal controls. These levels also appeared to correlate with the stage of the disease [67][68][69]. Like VOCs, EBC still requires further validation and large scale trials.…”
Section: Exhaled Breath Condensate (Ebc)mentioning
confidence: 89%